Intranigral Injection of Endotoxin Suppresses Proliferation of Hippocampal Progenitor Cells - Darwish, Batoul; Chamaa, Farah; Al-Chaer, Elie D.; Saadé, Nayef E.; Abou-Kheir, Wassim (Frontiers in Neuroscience, 2019)
Brain inflammation can result in functional disorders observed in several neurodegenerative diseases and that can be also associated with reduced neurogenesis. In this study, we investigate the effect of mild inflammation, induced by unilateral injection of Endotoxin (ET) in the substantia nigra (SN)/ ventral tegmental area (VTA), on the proliferation and survival of stem/progenitor cells in the dentate gyrus (DG) of the hippocampus. Adult female rats received unilateral injection of ET (2 µg/2 µl saline) or sterile saline (2 µl) in the right SN followed by 5’-Bromo-2’-deoxyuridine (BrdU) injections (66 mg/kg/injection). Intranigral ET injection induced bilateral decrease in the number of newly born BrdU positive cells in the DG. This effect was paralleled by a significant decrease in the exploratory behavior of rats, as assessed by the Y-maze novel arm exploration task. ET also induced a transient decrease in the number of tyrosine hydroxylase -positive cells in the injected SN, impaired motor behavior, and caused microglial activation in the SN. This study provides an experimental simulation of the remote effects of moderate and reversible neuroinflammation resulting in impaired communication between midbrain dopaminergic neurons and the hippocampus.